Effects of situation descriptions on the construct-related validity of construct-driven situational judgment tests - SCHAEPERS, Philipp Christopher (Institutional Knowledge at Singapore Management University, 2020)
Despite the common belief that situation descriptions in SJTs are central to the measurement of targeted constructs, recent studies demonstrated that omitting situation descriptions had only minor effects on SJT performance and validity. However, these results might be due to the fact that traditional SJTs often fail to assess well-defined constructs. So, we aimed to examine the relationships between construct-driven SJT scores with and without situations and self- and peer-rated personality dimensions (N = 158). Results revealed almost no difference in construct-related validity between both versions. The conscientiousness facet emerged as the only exception, for which the SJT scores without situation descriptions yielded a significantly higher convergent correlation.